Occurrence of work-related depression in the interior of Minas Gerais (Research, Society and Development, 2021)
To describe the occurrence of work-related depression notified in the interior of Minas Gerais and investigate the association between work-related depression and gender, age, situation in the labor market, working time in occupation and occupation category. A retrospective, descriptive and quantitative study, with analysis of all notifications of work-related depression accompanied in a public service specialized in worker health, from January 2013 to December 2019. The collected data was stored in Excel spreadsheets, in double entry with checking. For the data analysis, the Bioestat 5.0 program was used and for the categorical variables, the Chi-square test was used (α= 0.05). There was a predominance of female notifications. There was an association of depression with the female gender, specifically severe depression, with the situation in the work market and age group. There was no association of the disease to the occupational category. It is necessary to invest in strategies to promote and protect mental health in the work environment, especially among women who tend to have professional and family work days.